Fe-Cu bimetallic catalyst for the degradation of hazardous organic chemicals exemplified by methylene blue in Fenton-like reaction. Issue 5 (October 2020) - Nguyen, Thanh Binh; Dong, Cheng-Di; Huang, C.P.; Chen, Chiu-Wen; Hsieh, Shu-Ling; Hsieh, Shuchen
Graphical abstract: Highlights: Fe-Cu bimetallic composites of different Cu loadings were synthesized and characterized. Cu loading effectively controlled the size and distribution of bimetallic particles. Enhanced MB removal occurred over bimetallic Fe-Cu composites when Cu content was increased. Fe-Cu-080 exhibited high activity and stability in MB mineralization. EPR and FL results proved that the OH radicals was involved in MB degradation. Abstract: Fe-Cu bimetallic oxide, a Fenton-like catalyst, was synthesized by a facile co-precipitation method. The physicochemical characteristics of as-synthesized Fe-Cu bimetallic composites with different Cu mass loadings were characterized. The Fe-Cu-080 composite, having suitable amount of Cu, could effectively control the size of bimetallic particles, with uniform distribution in nano range, exhibited a higher activity and stability in methylene blue (MB) mineralization. Fe-Cu-080/H2 O2 system could work in a wide range pH with high efficiency in MB removal and low metal leaching concentration. Electron paramagnetic resonance (EPR) and fluorescence (FL) results proved that the OH radicals generated in Fe-Cu composite/H2 O2 system were involved in the degradation of methylene blue (MB). The Fe-Cu-080 catalyst could be easily separation from the aqueous solution by simple external magnetic field. Fe-Cu-080 was not cytotoxic and could greatly reduce the copper toxicity. The combination of Cu-Fe in bimetallic structure was proved to be an attractive alternative method to improve the efficiency of heterogeneous Fenton-like system exemplified by the removal of organic pollutants from wastewater.